2022
DOI: 10.1523/jneurosci.0656-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Causal Inference of Body Ownership in the Posterior Parietal Cortex

Abstract: How do we come to sense that a hand in view belongs to our own body or not? Previous studies have suggested that the integration of vision and somatosensation in the frontoparietal areas plays a critical role in the sense of body ownership (i.e., the multisensory perception of limbs and body parts as our own). However, little is known about how these areas implement the multisensory integration process at the computational level and whether activity predicts illusion elicitation in individual participants on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 80 publications
3
27
0
Order By: Relevance
“…Thus, the present results demonstrate that even small spatial changes within peripersonal space influence the strength of the illusion both in terms of sensitivity and bias. Again, this fits with a more continuous and probabilistic understanding of how spatial congruence influences the RHI, as opposed to a "fixed rule" with a distinct boundary, similar to the temporal rule as discussed above 24,39,110 .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Thus, the present results demonstrate that even small spatial changes within peripersonal space influence the strength of the illusion both in terms of sensitivity and bias. Again, this fits with a more continuous and probabilistic understanding of how spatial congruence influences the RHI, as opposed to a "fixed rule" with a distinct boundary, similar to the temporal rule as discussed above 24,39,110 .…”
Section: Discussionsupporting
confidence: 66%
“…We have recently scanned the RHI under a psychophysics detection task and found that activity in the premotor and posterior parietal cortices was related to illusion elicitation at the level of individual participants and trials. Moreover, activity in the posterior parietal cortex followed a Bayesian causal inference model's predicted probability of illusion emergence 110 . Thus, multisensory combination versus segregation performed by multisensory neuronal populations within frontoparietal circuits may implement the critical neuronal computations underlying the current findings of body ownership sensitivity and perceptual biases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important for the field of body representation to examine the robustness of this effect since it has theoretical implications for models of body ownership. A negative result would be similarly interesting because it would be in line with more parsimonious multisensory models of the RHI and body ownership that do not include motor processes or the primary motor cortex as a critical structure (Chancel, Iriye, & Ehrsson, 2022;Ehrsson, 2020;Fang et al, 2019;Guterstam et al, 2019;Kilteni et al, 2015;Samad, Chung, & Shams, 2015). Notably, Karabanov et al (2017) did not observe a reduction in corticospinal excitability as a consequence of the RHI, though they had a smaller sample size than della Gatta et al ( 2016) and used a slightly different paradigm (a moving version of the RHI).…”
Section: An Influential Article By Dellamentioning
confidence: 71%
“…One possibility is that they are simply a side effect of increased inhibitory output to the motor cortex from posterior parietal regions involved in multisensory body perception (Casula et al, 2022). Such an inhibitory influence could arise in some individuals purely from the strong structural and functional connectivity between the motor cortex and posterior parietal regions, the latter playing an important role in both motor control (Rizzolatti & Luppino, 2001) and multisensory integration during the RHI (Chancel et al, 2022;Ehrsson et al, 2004). One must be cautious in interpreting changes in corticospinal excitability in functional terms (Bestmann & Krakauer, 2015).…”
Section: Discussionmentioning
confidence: 99%